Требуются девушки для работы в Японии: [роман] / Юлия Шилова - Шилова Юлия Витальевна (Час криминала, 2000)
Экземпляры: ф.12 (20140305) / Инвентарный номер: 45648 / Цена: 50.00 / Авт.знак: Ш 59 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6